Molecular Detection of Occult Hepatitis B virus in plasma and urine of renal transplant patients in Khartoum state Sudan. (August 2020) - Ibrahim, Sabah A.E.; Mohamed, Sofia B.; Kambal, Sumaya; Diya-Aldeen, Aya; Ahmed, Sara; Faisal, Batool; Ismail, Fatima; Ibrahim, Amel; Sabawe, Amel; Mohamed, Osama
Highlights: The multiplex nested PCR had identified OBI with a high rate supporting the efficiency of using molecular techniques in detecting of HBV. This will lead to an appropriate diagnosis and minimizing the risk to be infected by HBV. Regarding the HBV genotypes, we found that the genotypes D, E and mixed D/E were present with higher rates rather than other HBV genotypes in Sudan, with genotype D being the dominant genotype. There is a high incidence of HBV among renal transplant patients, plasma samples showed more positive results than urine samples, the most infected were those younger than 30 and females were more infected than males. Abstract: Objective: The aim of this study was to determine the OBI in plasma and urine samples from renal transplant patients using Multiplex Nested PCR. Method: A total of 100 samples (plasma and urine) were collected from renal transplant patients admitted to the renal transplant center in Khartoum north, Sudan in 2019. For each sample, HBsAg, HBeAg and anti HBcAg were detected using Enzyme linked Immune sorbent assay (ELISA). The viral DNA was then extracted using viral DNA extraction kit and were then tested for HBV DNA by using multiplex nested PCR. Statistical analysis was done using statistical package of social science (IBM SPSS version 20.0) considering a P value ≤ 0.05 as a level of significance. Results: HBsAg were not detected in al patient but, HBeAg were 14 (14%) and anti HBcAg were 36 (36%)were detect by using ELISA. A total 18 (18%) and 3 out of 100 were found positive in plasma and urine samples, respectively. Regarding the virus genotypes, D, E and mixed D/E genotypes were detected in all positive samples. Females were significantly (P value = 0.013) higher detectable with HBV than males in plasma samples Conclusion: OBI incidence in renal transplant patients is high in Sudan. The multiplex nested PCR had identified OBI with a high rate supporting the efficiency of using molecular techniques in detecting of HBV. This will lead to an appropriate diagnosis and minimizing the risk to be infected by HBV.